On the Absolute Summability Factors of Infinite Series involving Quasi-f-power Increasing Sequence - Sulaiman, W. T. (Journal of Informatics and Mathematical Sciences, 2012)
In this note we improve a result concerning absolute summability factor of an infinite series via quasi $β$-power increasing sequence achieved by Sevli and Leindler [1].